Wnt/β-catenin activation by mutually exclusive FBXW11 and CTNNB1 hotspot mutations drives salivary basal cell adenoma - Wong, Kim; Bishop, Justin A.; Weinreb, Ilan; Motta, Marialetizia; Del Castillo Velasco-Herrera, Martin; Bellacchio, Emanuele; Ferreira, Ingrid; van der Weyden, Louise; Boccacino, Jacqueline M.; Lauri, Antonella; Rotundo, Giovannina; Ciolfi, Andrea; et al. (Nature Communications, 2025)
Basal cell adenoma (BCA) and basal cell adenocarcinoma (BCAC) of the salivary gland are rare tumours that can be difficult to distinguish from each other and other salivary gland tumour subtypes. Using next-generation sequencing, we identify a recurrent FBXW11 missense mutation (p.F517S) in BCA that is mutually exclusive with the previously reported CTNNB1 p.I35T gain-of-function (GoF) mutation with these mutations collectively accounting for 94% of BCAs. In vitro, mutant FBXW11 is characterised by defective binding to β-catenin and higher protein levels within the nucleus. This is consistent with the increased nuclear expression of β-catenin and activation of the Wnt/β-catenin pathway. The genomic profiles of BCAC are distinct from BCA, with hotspot DICER1 and HRAS mutations and putative driver mutations affecting PI3K/AKT and NF-κB signalling pathway genes. These findings have important implications for the diagnosis and treatment of BCA and BCAC, which, despite histopathologic overlap, may be unrelated entities.